TRANSFORMASI BRANDING UMKM KRUPUK MELALUI INTEGRASI DESAIN KEMASAN KREATIF DAN STORYTELLING PRODUK DI KECAMATAN PATI - Teguh Setiadi; Eka Satria Wibawa; Priyadi Priyadi; Bagus Sudirman; Robby Andika Kusumajaya; Sri Kawuri (Jurnal Padamu Negeri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, but still face challenges in branding, particularly in packaging design and conveying product value. This community service activity aims to improve the competitiveness of MSMEs through branding transformation with the integration of creative product packaging design and storytelling. The partner in this activity is the mackerel fish cracker MSME of Mr Siwito Wahono, located in Pati Lor Village, Pati District, Pati Regency. The method used is a participatory approach through the stages of observation, planning, training, mentoring, and evaluation. The results of the activity show an increase in partners' understanding of branding, with an average increase of 36% based on the results of the pre-test and post-test. In addition, this activity produces outputs in the form of new, more attractive packaging designs, brand identities (logos and labels), and product storytelling that can strengthen the value and uniqueness of the product. The integration of packaging design and storytelling has proven effective in increasing the visual appeal and emotional value of the product, thus potentially increasing the competitiveness of MSMEs in the market. Therefore, this community service activity makes a real contribution to the development of MSME branding practically and sustainably.